Follow up study of labial salivary gland lesions in primary Sjögren's syndrome. Issue 6 (June 1992) - Leroy, J P; Pennec, Y L; Soulier, C; Berthelot, J M; Letoux, G; Youinou, P
Abstract : Labial salivary gland biopsy samples were taken from 27 patients with primary Sjögren's syndrome (SS), 10 with rheumatoid arthritis (RA) and secondary SS, and four normal control subjects on two occasions at intervals of more than one year. In the former group of patients, eight of the nine initially negative analyses were positive on the second sample, whereas two of the seven patients with RA and secondary SS were negative for the first sample and then positive for the second. In primary SS, the mean (SD) variation of the focus score was 1.7 (2.6) and that of salivary duct infiltration 0.2 (0.7). The former correlated well with the latter.